Cognition, social cognition and functioning in schizophrenia. - Vaz-Serra, Adriano (2010)
The major reviews of the literature support the idea that a significant proportion of patients with schizophrenia present cognitive deficits in several domains, more marked in the domains of verbal memory, vigilance and attention, memory, intellectual quotient, language and executive functioning. Such deficits appear to be one of the main determinants of these patients' functional outcome. More recently, social cognition deficits have been described. Social cognition may be understood as a separate and independent dimension of neurocognition or non-social cognition and may constitute a mediator between the neurocognition and functioning. However, there has been controversy concerning the real meaning of deficits observed due to the diversity of analysis methodologies employed and the fact that the available neuropsychological tests and batteries have not been specifically designed to evaluate cognitive deficits in patients with schizophrenia. In this paper, the Working Group on Schizophrenia (GTE) describes and highlights the existing clinical and scientific evidence, performs a critical review of cognitive functioning, social cognition and its impact on functional outcome, in patients with schizophrenia. The authors review definitions of (neuro)cognition, social cognition and functioning, analyze the existing methods for its assessment, describe the treatments available in this context and summarize the evidence of dysfunctions in these three concepts, taking into account their interconnection. Overall, the GTE considered the need for a standardized battery of tests to measure neurocognition, social cognition and functioning, consensually accepting the use of MATRICS as the standard tool for assessing neurocognition in schizophrenia. It was also recognized that verbal memory and vigilance deficits may be the best predictors of functional outcome in schizophrenia. In addition, the GTE has established social cognition as a priority area in the study of schizophrenia, however, the limitations in terminology and assessment methodologies do not allow a consensus in this area. The GTE considers that further longitudinal studies with larger samples are needed, so that a more adequate therapeutic armamentarium becomes available for patients with schizophrenia.